High-permeability hydrolysis-resistant film and preparation method thereof

By adding calcium carbonate and PDMS as anti-hydrolysis inhibiting additives and capping agents during PET polyester synthesis, and spraying PDMS/SiO2 hydrophobic coating on the surface of the film, the problem of insufficient hydrolysis resistance of PET polyester film is solved, and the problem of insufficient hydrolysis resistance of PET polyester film is achieved. High light transmission and high hydrolysis resistance film properties.

CN119431860APending Publication Date: 2025-02-14TAICANG SIDIKE NEW MATERIALS SCI & TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411542718.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has problems of waste of resources, high costs and degradation of performance in improving the hydrolysis resistance of PET polyester films, especially in the esterification reaction and post-processing process.

Method used

The anti-adhesive calcium carbonate is added as an anti-hydrolysis inhibitor during the polyester synthesis process, and the capping agent PDMS is added after the synthesis is completed, and the content of the mid-term carboxyl group of the polyester is controlled, while the PDMS/SiO2 hydrophobic coating is sprayed on the film surface. layer, forming a superhydrophobic surface.

Benefits of technology

The high light transmission and high hydrolysis resistance of polyester films are achieved, which delays water vapor erosion, reduces the risk of internal hydrolysis of polyester, and improves the adhesion and optical transmittance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113140120000151
    Figure BDA0005113140120000151
  • Figure BDA0005113140120000161
    Figure BDA0005113140120000161
Patent Text Reader

Abstract

The invention discloses a high-permeability hydrolysis-resistant film and a preparation method thereof. The method comprises the following steps: S1, preparing hydrolysis-resistant master batches; the hydrolysis-resistant master batch is prepared from the following raw materials: nano SiO2, nano CaCO3, ethylene glycol, terephthalic acid, an esterification polycondensation catalyst, a buffer agent, a stabilizer and an end-capping reagent; s2, preparing a base film from the hydrolysis-resistant master batch through melt extrusion; s3, hydrophobic paint is sprayed on the base film to form a hydrophobic layer, and the high-permeability hydrolysis-resistant film is prepared. The anti-sticking agent calcium carbonate is added in the polyester synthesis process and serves as a hydrolysis inhibitor for consuming terminal carboxyl groups in the polyester, and the end-capping reagent PDMS is added after polyester esterification polycondensation is finished, that is, unreacted terminal carboxyl groups are consumed before discharging, so that the risk of internal hydrolysis of the polyester in the discharging and subsequent processing processes can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyester film materials, and in particular to a high-transparency and hydrolysis-resistant film and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) is a resin formed by combining terephthalic acid and ethylene glycol. It has the advantages of strong plasticity, convenient processing, low cost, and good film-forming properties. It is currently widely used in engineering plastics, product packaging, electrical insulation materials, automotive exterior parts and other fields. However, the main chain of the PET molecule contains a large number of ester bonds, which will decompose under the action of strong acids, strong bases and water vapor, and terminal carboxyl groups will appear. The terminal carboxyl groups will continue to promote the decomposition of ester bonds, accelerate the aging of PET itself, and cause the mechanical, optical and appearance of the material to deteriorate. The terminal carboxyl groups in the polyester molecular chain generally come from two aspects, one is the unreacted terminal carboxyl groups, and the other is the terminal carboxyl groups generated by degradation. Therefore, the optimization of PET hydrolysis resistance is generally achieved from the following two ways. The first way is to improve the synthesis end, that is, to interfere before the polyester is discharged; the second way is to improve after synthesis, that is, to perform secondary treatment on the polyester with normal terminal carboxyl content during the later processing and molding process.

[0003] In a patented method for preparing a hydrolysis-resistant polyester film (CN 109081929 B), the molar ratio of the synthetic terminal diol to the dibasic acid is controlled to be above 1.3, and a titanium catalyst is used to assist in promoting the consumption of the terminal carboxyl groups of the dibasic acid itself during the esterification polycondensation reaction, thereby obtaining a polyester with high viscosity and low terminal carboxyl content. However, according to this method, there must be an excessive amount of diol in the reaction system, resulting in a waste of diol resources. More importantly, during the esterification reaction stage, under the action of the titanium catalyst and hydrogen ions H+, the diol undergoes hydroxyl dehydration condensation to generate diethylene glycol with an ether bond. Diethylene glycol is embedded in the PET molecular chain in the form of a chain segment, destroying the regularity of the molecular chain, resulting in a decrease in the melting point of PET and a decrease in light and heat resistance.

[0004] The patent "High barrier and hydrolysis resistant solar cell back panel and its preparation method" (CN 111477711B) reports an improvement method of adding exfoliated modified mica sheets during the in-situ polymerization of PET polyester, that is, the mica sheets are evenly dispersed in the polyester film in the form of nano-thin sheets, and the layered structure of the mica sheets makes the path of water vapor molecules tortuous, which significantly improves the water vapor barrier performance of the polyester film. The amount of mica sheets added to the polyester prepared by this method accounts for 1%-5% of the dibasic acid, and the average particle size is 3-10μm, which may lead to problems such as crystal points and film breakage during the later biaxial stretching process of polyester, and the modification process is relatively complicated and costly.

[0005] Patent A high-performance anti-hydrolysis PET masterbatch and its preparation method (CN 103627152 A) reports a high-efficiency anti-hydrolysis PET that is mixed with a carbodiimide anti-hydrolysis agent and then extruded by a screw. The shear force of the twin-screw extruder is large, which will cause part of the carbodiimide anti-hydrolysis agent to react with the PET or degrade, produce toxic gases, and affect the performance of the polyester.

[0006] Patented modified PET polyester material, solar cell backplane film and application of ultraviolet absorber (CN 113321904B) mentions that adding a carbodiimide anti-hydrolysis agent to a PET resin substrate will promote yellowing of the resin, and further mentions a method of adding an ultraviolet absorber to reduce the yellowing index of the PET resin material. However, the addition of the ultraviolet absorber will cause the PET substrate to turn green, thereby reducing the red light transmittance, resulting in a reduction in the light-to-heat conversion efficiency during the operation of the solar cell backplane.

[0007] The above-mentioned preparation methods of hydrolysis-resistant PET have basically realized the hydrolysis-resistant functionalization of PET, but there is still room for optimization. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a high-transparency and hydrolysis-resistant film and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: In a first aspect of the present invention, a method for preparing a high-transmittance and hydrolysis-resistant film is provided, comprising the following steps:

[0010] S1, preparing hydrolysis-resistant masterbatch;

[0011] The raw materials for preparing the hydrolysis-resistant masterbatch include: nano-SiO 2 、Nano-CaCO 3 , ethylene glycol, terephthalic acid, esterification polycondensation catalyst, buffer, stabilizer, capping agent;

[0012] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0013] S3. Spray a hydrophobic coating on the base film to form a hydrophobic layer, thereby preparing a highly transparent and hydrolysis-resistant film.

[0014] Preferably, step S1 specifically includes:

[0015] S1-1, take 15-40wt% of nano-SiO 2 With nano-CaCO 3 The mixture of 60-85wt% ethylene glycol is put into a sand mill and sand milled at 400-1600r / min for 3-12h to obtain a nanoparticle dispersion slurry, wherein the nano-SiO2 With nano-CaCO 3 The mass ratio is 2:1-1:2;

[0016] S1-2, weigh nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1-1.5, and the nano-SiO 2 With nano-CaCO 3 The mixture has a total content of 1500-6000 ppm relative to terephthalic acid;

[0017] Adding 80-350 ppm of esterification polycondensation catalyst, 35-140 ppm of buffer and 150-600 ppm of stabilizer to the nanoparticle dispersion slurry relative to the terephthalic acid content, stirring evenly and then putting it into a reactor, then putting terephthalic acid into the reactor, and finally adding ethylene glycol;

[0018] S1-3, after sealing the reactor, introduce nitrogen and react at 240-250°C. When the water output reaches more than 95% of the theoretical water output, heat it to 275-285°C and simultaneously evacuate the reactor for polycondensation. React for 130-170 minutes and discharge the material. Add a capping agent accounting for 5-20 mol% of the total terephthalic acid content 2-10 minutes before discharging the material to obtain a hydrolysis-resistant masterbatch.

[0019] Preferably, step S1 specifically includes:

[0020] S1-1, take 25wt% of nano-SiO 2 With nano-CaCO 3 The mixture of 75wt% ethylene glycol was put into a sand mill and sand milled at 800r / min for 6h to obtain a nanoparticle dispersion slurry, wherein nano-SiO 2 With nano-CaCO 3 The mass ratio is 1:1;

[0021] S1-2, weigh nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, satisfying the molar ratio of ethylene glycol to terephthalic acid of 1.25, and the nano-SiO 2 With nano-CaCO 3 The total content of the mixture relative to terephthalic acid is 3000ppm;

[0022] An esterification polycondensation catalyst with a content of 170 ppm relative to terephthalic acid, a buffer of 70 ppm, and a stabilizer of 300 ppm are added to the nanoparticle dispersion slurry, and after being stirred evenly, the mixture is put into a reactor, and then terephthalic acid is put into the reactor, and finally ethylene glycol is added;

[0023] S1-3, nitrogen is introduced into the closed reactor, and the reaction is carried out at 240-250°C. When the water output reaches more than 95% of the theoretical water output, the temperature is raised to 275-285°C, and vacuum is drawn to carry out polycondensation reaction. The reaction lasts for 130-170 minutes and the material is discharged. 5 minutes before the discharge, a capping agent accounting for 5-20 mol% of the total terephthalic acid content is added to obtain a hydrolysis-resistant masterbatch.

[0024] Preferably, the esterification polycondensation catalyst is selected from at least one of titanium glycolate (Ti(EG)2), titanium dioxide (TiO2), antimony glycolate (Sb2(EG)3), antimony oxide (Sb2O3), germanium oxide (GeO2), sodium aluminate (NaAlO2), and sodium aluminosilicate (AlNaO6Si2);

[0025] The buffer is selected from one or more of hydroxyethylpiperazineethionine (HEPES) buffer, phosphate buffer, and 2-morpholineethylsulfonic acid (MES) buffer.

[0026] Preferably, the stabilizer is selected from at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, and triethyl phosphoacetate;

[0027] The end-capping agent is selected from at least one of KH550, KH560, polydimethylsiloxane, and anilinemethyltriethoxysilane.

[0028] Preferably, the raw materials for preparing the hydrophobic coating include, by weight:

[0029] 500-2000 parts of solvent, 50-200 parts of modifier, 12-50 parts of nano-SiO 2 , 2-8 parts of organosilane, 0.1-2 parts of modified catalyst, 0.5-2 parts of antioxidant.

[0030] Preferably, step S3 specifically includes:

[0031] S3-1, preparation of hydrophobic coating:

[0032] Mix and disperse the solvent and modifier for 5-20 minutes, then add nano-SiO 2 Disperse for 5-30 minutes, add organosilane, modified catalyst and antioxidant, stir for 0.5-2 minutes, and stand for 10-40 minutes to defoam to obtain a hydrophobic coating;

[0033] S3-2, coating the hydrophobic coating on the upper and lower surfaces of the cleaned base film, baking at 70-90° C. for 2-10 minutes to form a hydrophobic layer with a thickness of 65-90 nm, and obtaining a highly transparent and hydrolysis-resistant film.

[0034] Preferably, the solvent is selected from at least one of toluene, ethyl acetate, alcohol and butanone;

[0035] The modifier is selected from at least one of tert-butyl acrylate, polydimethylsiloxane (PDMS), and polydimethylsiloxane copolymer;

[0036] The organosilane is selected from one of methyltriethoxysilane and tetraethoxysilane (TEOS);

[0037] The antioxidant is selected from at least one of alkyl dithiocarbamate zinc, mercaptobenzothiazole derivatives, and benzotriazole derivatives;

[0038] The modified catalyst is dibutyl butyl dilaurate.

[0039] Preferably, step S2 specifically comprises: melt-extrude the hydrolysis-resistant polyester masterbatch at 260-300° C., quench with a cold roller at 40-60° C. to obtain an amorphous casting sheet, and then biaxially stretch it to obtain a base film.

[0040] The second aspect of the present invention provides a high-transmittance and hydrolysis-resistant film, which is prepared by the method as described above.

[0041] The beneficial effects of the present invention are:

[0042] The present invention provides a simple and efficient process for synthesizing hydrolysis-resistant polyester, and a method for preparing a hydrophobic surface-treated high-transparency PET hydrolysis-resistant film with a relatively fast production speed;

[0043] The present invention adds an anti-adhesive calcium carbonate during the polyester synthesis process, which also serves as a hydrolysis inhibitor that consumes the terminal carboxyl groups in the polyester, and adds a capping agent PDMS after the polyester esterification polycondensation is completed, that is, the unreacted terminal carboxyl groups are consumed before discharging, thereby reducing the risk of internal hydrolysis of the polyester during discharging and subsequent processing.

[0044] The present invention sprays PDMS / SiO2 with appropriate thickness on the surface of polyester film. 2 The coating (i.e., hydrophobic layer) forms a highly transparent coating with a sub-micron-nano binary structure on the surface. The hydrophobicity and surface roughness of the composite coating produce super-hydrophobicity, which delays water vapor erosion. The polyester contains PDMS as a capping agent, which strengthens the PDMS / SiO 2 The adhesion of the coating; if the coating thickness is too small, the surface nanoparticles will be reduced, unable to cover the surface and form an appropriate super-hydrophobic surface roughness; if the coating thickness is too large, the surface light resistance will increase and the optical transmittance and clarity will decrease.

[0045] The present invention can expand the application field of the polyester optical film, such as some high-humidity environments, by strengthening the anti-hydrolysis ability of the polyester film itself and spraying a high-transparency hydrophobic film on the surface to achieve water isolation. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0047] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0048] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0049] The present invention provides a high-transparency and hydrolysis-resistant film and a preparation method thereof, the method comprising the following steps:

[0050] S1, preparing hydrolysis-resistant masterbatch;

[0051] The raw materials for the preparation of hydrolysis-resistant masterbatch include: nano-SiO 2 、Nano-CaCO 3 , ethylene glycol, terephthalic acid, esterification polycondensation catalyst, buffer, stabilizer, capping agent;

[0052] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0053] S3. Spray a hydrophobic coating on the base film to form a hydrophobic layer, thereby preparing a highly transparent and hydrolysis-resistant film.

[0054] In a preferred embodiment, step S1 specifically includes:

[0055] S1-1, take 15-40wt% of nano-SiO 2 With nano-CaCO 3 The mixture of 60-85wt% ethylene glycol is put into a sand mill and sand milled at 400-1600r / min for 3-12h to obtain a nanoparticle dispersion slurry, wherein the nano-SiO 2 With nano-CaCO 3 The mass ratio is 2:1-1:2;

[0056] S1-2, weigh nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1-1.5, and the nano-SiO 2 With nano-CaCO 3 The mixture has a total content of 1500-6000 ppm relative to terephthalic acid;

[0057] Adding 80-350 ppm of esterification polycondensation catalyst, 35-140 ppm of buffer and 150-600 ppm of stabilizer to the nanoparticle dispersion slurry relative to the terephthalic acid content, stirring evenly and then putting it into a reactor, then putting terephthalic acid into the reactor, and finally adding ethylene glycol;

[0058] S1-3, nitrogen is introduced into the closed reactor, and the reaction is carried out at 240-250° C. When the water output reaches more than 95% of the theoretical water output, the temperature is raised to 275-285° C. and vacuum is drawn to carry out polycondensation reaction. The reaction is carried out for 130-170 minutes and the material is discharged. 2-10 minutes before the discharge, a capping agent accounting for 5-20 mol% (molar percentage) of the total content of terephthalic acid is added to obtain a hydrolysis-resistant masterbatch.

[0059] In a more preferred embodiment, step S1 specifically includes:

[0060] S1-1, take 25wt% of nano-SiO 2 With nano-CaCO 3 The mixture of 75wt% ethylene glycol was put into a sand mill and sand milled at 800r / min for 6h to obtain a nanoparticle dispersion slurry, wherein nano-SiO 2 With nano-CaCO 3 The mass ratio is 1:1;

[0061] S1-2, weigh nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, satisfying the molar ratio of ethylene glycol to terephthalic acid of 1.25, and the nano-SiO 2 With nano-CaCO 3 The total content of the mixture relative to terephthalic acid is 3000ppm;

[0062] An esterification polycondensation catalyst with a content of 170 ppm relative to terephthalic acid, a buffer of 70 ppm, and a stabilizer of 300 ppm are added to the nanoparticle dispersion slurry, and after being stirred evenly, the mixture is put into a reactor, and then terephthalic acid is put into the reactor, and finally ethylene glycol is added;

[0063] S1-3, nitrogen is introduced into the closed reactor, and the reaction is carried out at 240-250°C. When the water output reaches more than 95% of the theoretical water output, the temperature is raised to 275-285°C, and vacuum is drawn to carry out polycondensation reaction. The reaction lasts for 130-170 minutes and the material is discharged. 5 minutes before the discharge, a capping agent accounting for 5-20 mol% of the total terephthalic acid content is added to obtain a hydrolysis-resistant masterbatch.

[0064] In a preferred embodiment, nano-SiO 2Selected from HM031 provided by Jiangsu Huimai Powder Technology Co., Ltd., HS-30 from Grace, Brofos-SiO 2 -50, TSP-C09 of Jiangsu Tianxing New Materials Co., Ltd., KR-SiO 2 -1 one or more.

[0065] In a preferred embodiment, nano-CaCO 3 Selected from one or more of KL3 / SO57A of Guangxi Kelong Powder, TC10 of Guangxi Kelong Powder, GY-316 of Jiangxi Guangyuan Chemical Co., Ltd., and JD-626 of Anhui Jiangdong Technology Powder Co., Ltd.

[0066] In a preferred embodiment, ethylene glycol is selected from one or more provided by Sinopec Yangzi Petrochemical Co., Ltd., Shanghai Hongzhuang Chemical Technology Co., Ltd., Danhua Chemical Technology Co., Ltd., and Guangzhou Haoyi New Materials Technology Co., Ltd.

[0067] In a preferred embodiment, terephthalic acid is selected from one or more provided by Hengli Petrochemical Co., Ltd., Zhejiang Yisheng Petrochemical Co., Ltd., Guangzhou Haoyi New Materials Technology Co., Ltd., and Rongsheng Petrochemical Co., Ltd.

[0068] In a preferred embodiment, the esterification polycondensation catalyst is selected from the Ti-based catalyst titanium ethylene glycol (Ti(EG) 2 ), titanium dioxide (TiO 2 ), Sb-based catalyst antimony glycolate (Sb 2 (EG) 3 ), antimony oxide (Sb 2 O 3 ), Ge-based catalyst germanium oxide (GeO 2 ), Al-based catalyst sodium aluminate (NaAlO 2 ), sodium aluminosilicate (AlNaO 6 Si 2 ) at least one of.

[0069] In a preferred embodiment, the buffer is selected from one or more of hydroxyethylpiperazineethionine (HEPES) buffer, phosphate buffer, and 2-morpholineethylsulfonic acid (MES) buffer.

[0070] In a preferred embodiment, the stabilizer is selected from at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, and triethyl phosphoacetate.

[0071] In a preferred embodiment, the end-capping agent is selected from at least one of KH550, KH560, polydimethylsiloxane, and anilinemethyltriethoxysilane.

[0072] In a preferred embodiment, the raw materials for preparing the hydrophobic coating include, by weight:

[0073] 500-2000 parts of solvent, 50-200 parts of modifier, 12-50 parts of nano-SiO 2 , 2-8 parts of organosilane, 0.1-2 parts of modified catalyst, 0.5-2 parts of antioxidant.

[0074] In a preferred embodiment, step S3 specifically includes:

[0075] S3-1, preparation of hydrophobic coating:

[0076] Mix and disperse the solvent and modifier for 5-20 minutes, then add nano-SiO 2 Disperse for 5-30 minutes, add organosilane, modified catalyst and antioxidant, stir for 0.5-2 minutes, and let stand for 10-40 minutes to defoam to obtain a hydrophobic coating.

[0077] S3-2, coating the hydrophobic coating on the upper and lower surfaces of the cleaned base film, baking at 70-90° C. for 2-10 minutes to form a hydrophobic layer with a thickness of 65-90 nm, and obtaining a highly transparent and hydrolysis-resistant film.

[0078] In a preferred embodiment, the solvent is selected from at least one of toluene, ethyl acetate, alcohol and butanone.

[0079] In a preferred embodiment, the modifier is selected from at least one of tert-butyl acrylate, polydimethylsiloxane (PDMS), and polydimethylsiloxane copolymer.

[0080] In a preferred embodiment, the organosilane is selected from methyltriethoxysilane and tetraethoxysilane (TEOS).

[0081] In a preferred embodiment, the antioxidant is selected from at least one of zinc alkyldithiocarbamate, mercaptobenzothiazole derivatives, and benzotriazole derivatives.

[0082] In a preferred embodiment, the modified catalyst is dibutyl butyl dilaurate.

[0083] In a preferred embodiment, step S2 specifically comprises: melt-extrude the hydrolysis-resistant polyester masterbatch at 260-300° C., quench with a cold roller at 40-60° C. to obtain an amorphous casting sheet, and then biaxially stretch it to obtain a base film.

[0084] The CaCO added in the present invention 3 It can be used not only as an anti-adhesive agent, but also as an anti-hydrolysis inhibitor.

[0085] The present invention controls the terminal carboxyl content of the polyester masterbatch by adding an anti-hydrolysis inhibitor and a terminal carboxyl capping agent from the synthesis end, and combines the method of spraying a hydrophobic layer on the surface after film formation to slow down the aging speed of the polyester optical film in a humid environment.

[0086] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0087] In the following examples and comparative examples, nano-SiO 2 Selected from HM031 provided by Jiangsu Huimai Powder Technology Co., Ltd., nano-CaCO 3 KL3 / SO57A selected from Guangxi Kelong Powder and TC10 from Guangxi Kelong Powder, ethylene glycol was purchased from Sinopec Yangzi Petrochemical Co., Ltd., and terephthalic acid was purchased from Hengli Petrochemical Co., Ltd.

[0088] Example 1

[0089] A method for preparing a highly transparent and hydrolysis-resistant film, characterized in that it comprises the following steps:

[0090] S1. Preparation of hydrolysis-resistant masterbatch:

[0091] S1-1, according to the weight percentage, 25% of nano-SiO 2 / CaCO 3 Powder and 75% ethylene glycol solvent were put into the sand mill, among which SiO 2 、CaCO 3 The ratio was 1:1, the sand milling speed was set to 800 r / min, the sand milling time was 6 h, and the nanoparticle dispersion slurry was prepared for use;

[0092] S1-2, weigh a certain amount of nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1.25, and the nano-SiO 2 With nano-CaCO 3 The total content of the mixture relative to terephthalic acid is 3000ppm;

[0093] The esterification polycondensation catalyst Sb with a content of 170 ppm relative to terephthalic acid 2 O 3 , 70ppm buffer NaH 2 PO 4 300ppm of stabilizer trimethyl phosphate is added to the nanoparticle dispersion slurry, stirred evenly and then put into the reactor, then terephthalic acid is slowly added into the reactor through the feed port, and finally ethylene glycol is added;

[0094] S1-3. After closing the reactor, nitrogen is slowly introduced, and the esterification temperature in the kettle is set to 245°C (the actual temperature is between 230 and 245°C) for reaction. When the water output reaches 95% of the theoretical water output, the esterification valve is turned off, and the pressure relief valve is opened to make the pressure in the kettle reach atmospheric pressure, and then the temperature is raised to 280°C, and the vacuum degree of the polymerization system is reduced by evacuation. When the vacuum degree of the system reaches 20Pa, the temperature is raised to 280°C, and the reaction is carried out for 150 minutes to discharge the material. 5 minutes before discharging, a capping agent PDMS accounting for 10 mol% of the total content of terephthalic acid is added to obtain an anti-hydrolysis masterbatch.

[0095] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0096] The anti-hydrolysis masterbatch was added into the melt extrusion system, melted at 280°C and then extruded, and quenched on a cold roller at 50°C to obtain an amorphous casting sheet with a thickness of 500 μm, and then the casting sheet was pulled into a stretching area, and the casting sheet was biaxially stretched by 2.0 times, and the film thickness after stretching was 125 μm to obtain a base film;

[0097] S3, spraying a hydrophobic coating on the base film to form a hydrophobic layer, and preparing a highly transparent and hydrolysis-resistant film:

[0098] S3-1, preparation of hydrophobic coating:

[0099] In terms of weight, a mixture of 1000 parts of ethyl acetate and 100 parts of polydimethylsiloxane was dispersed using an emulsifier for 10 minutes, and then 25 parts of nano-SiO 2 , SiO 2 After adding completely, continue to disperse for 15 minutes to form a uniform suspension, then add 4 parts of tetraethoxysilane, 1 part of dibutyl butyl dilaurate catalyst, and 1 part of benzotriazole derivative antioxidant Tinuvin 327 (2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole) and continue stirring for 1 minute. After the end, let it stand for 20 minutes to defoam to obtain a hydrophobic coating.

[0100] S3-2. Pre-clean the surface of the base film obtained above to remove surface dust, grease, etc., and then apply the hydrophobic coating on both sides of the base film at a distance of 35 cm by machine spraying. Then, place the composite film containing the coating liquid in an oven at 80°C and bake for 5 minutes to form a hydrophobic layer with a thickness of 75 nm, and finally obtain a highly transparent and hydrolysis-resistant film.

[0101] Comparative Example 1

[0102] S1. Preparation of hydrolysis-resistant masterbatch:

[0103] S1-1, according to the weight percentage, 25% of nano-SiO 2 / CaCO 3Powder and 75% ethylene glycol solvent were put into the sand mill, among which SiO 2 、CaCO 3 The ratio was 1:1, the sand milling speed was set to 800 r / min, the sand milling time was 6 h, and the nanoparticle dispersion slurry was prepared for use;

[0104] S1-2, weigh a certain amount of nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1.25, and the nano-SiO 2 With nano-CaCO 3 The total content of the mixture relative to terephthalic acid is 3000ppm;

[0105] The esterification polycondensation catalyst Sb with a content of 170 ppm relative to terephthalic acid 2 O 3 , 70ppm buffer NaH 2 PO 4 300ppm of stabilizer trimethyl phosphate is added to the nanoparticle dispersion slurry, stirred evenly and then put into the reactor, then terephthalic acid is slowly added into the reactor through the feed port, and finally ethylene glycol is added;

[0106] S1-3. After closing the reactor, nitrogen is slowly introduced, and the esterification temperature in the kettle is set to 245°C (the actual temperature is between 230 and 245°C) for reaction. When the water output reaches 95% of the theoretical water output, the esterification valve is turned off, and the pressure relief valve is opened to make the pressure in the kettle reach atmospheric pressure, and then the temperature is raised to 280°C, and the vacuum degree of the polymerization system is reduced by evacuation. When the vacuum degree of the system reaches 20Pa, the temperature is raised to 280°C, and the reaction is carried out for 150 minutes to discharge the material. 5 minutes before discharging, a capping agent PDMS accounting for 10 mol% of the total content of terephthalic acid is added to obtain an anti-hydrolysis masterbatch.

[0107] S2. Add the anti-hydrolysis masterbatch into the melt extrusion system, melt it at 280°C and then extrude it, and quench it on a cold roller at 50°C to obtain an amorphous cast sheet with a thickness of 500 μm. Then, the cast sheet is pulled to the stretching area and biaxially stretched by 2.0 times. After stretching, the film thickness is 125 μm, and a high-transparency anti-hydrolysis film is obtained.

[0108] Comparative Example 2

[0109] A method for preparing a highly transparent and hydrolysis-resistant film, characterized in that it comprises the following steps:

[0110] S1. Preparation of hydrolysis-resistant masterbatch:

[0111] S1-1, according to the weight percentage, 25% CaCO 3The powder and 75% ethylene glycol solvent were put into a sand mill, the sand mill speed was set to 800 r / min, the sand mill time was 6 h, and the nanoparticle dispersion slurry was prepared for use;

[0112] S1-2, weigh a certain amount of nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, satisfying the molar ratio of ethylene glycol to terephthalic acid of 1.25, and the nanoparticle dispersion slurry contains nano-CaCO 3 Relative to the total terephthalic acid content of 3000ppm;

[0113] The esterification polycondensation catalyst Sb with a content of 170 ppm relative to terephthalic acid 2 O 3 , 70ppm buffer NaH 2 PO 4 300ppm of stabilizer trimethyl phosphate is added to the nanoparticle dispersion slurry, stirred evenly and then put into the reactor, then terephthalic acid is slowly added into the reactor through the feed port, and finally ethylene glycol is added;

[0114] S1-3. After closing the reactor, nitrogen is slowly introduced, and the esterification temperature in the kettle is set to 245°C (the actual temperature is between 230 and 245°C) for reaction. When the water output reaches 95% of the theoretical water output, the esterification valve is turned off, and the pressure relief valve is opened to make the pressure in the kettle reach atmospheric pressure, and then the temperature is raised to 280°C, and the vacuum degree of the polymerization system is reduced by evacuation. When the vacuum degree of the system reaches 20Pa, the temperature is raised to 280°C, and the reaction is carried out for 150 minutes to discharge the material. 5 minutes before discharging, a capping agent PDMS accounting for 10 mol% of the total content of terephthalic acid is added to obtain an anti-hydrolysis masterbatch.

[0115] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0116] The anti-hydrolysis masterbatch was added into the melt extrusion system, melted at 280°C and then extruded, and quenched on a cold roller at 50°C to obtain an amorphous casting sheet with a thickness of 500 μm, and then the casting sheet was pulled into a stretching area, and the casting sheet was biaxially stretched by 2.0 times, and the film thickness after stretching was 125 μm to obtain a base film;

[0117] S3, spraying a hydrophobic coating on the base film to form a hydrophobic layer, and preparing a highly transparent and hydrolysis-resistant film:

[0118] S3-1, preparation of hydrophobic coating:

[0119] In terms of weight, a mixture of 1000 parts of ethyl acetate and 100 parts of polydimethylsiloxane was dispersed using an emulsifier for 10 minutes, and then 25 parts of nano-SiO 2 , SiO 2After adding completely, continue to disperse for 15 minutes to form a uniform suspension, then add 4 parts of tetraethoxysilane, 1 part of dibutyl butyl dilaurate catalyst, and 1 part of benzotriazole derivative antioxidant Tinuvin 327 (2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole) and continue stirring for 1 minute. After the end, let it stand for 20 minutes to defoam to obtain a hydrophobic coating.

[0120] S3-2. Pre-clean the surface of the base film obtained above to remove surface dust, grease, etc., and then apply the hydrophobic coating on both sides of the base film at a distance of 35 cm by machine spraying. Then, place the composite film containing the coating liquid in an oven at 80°C and bake for 5 minutes to form a hydrophobic layer with a thickness of 75 nm, and finally obtain a highly transparent and hydrolysis-resistant film.

[0121] Comparative Example 3

[0122] A method for preparing a highly transparent and hydrolysis-resistant film, characterized in that it comprises the following steps:

[0123] S1. Preparation of hydrolysis-resistant masterbatch:

[0124] S1-1, according to the weight percentage, 25% of nano-SiO 2 The powder and 75% ethylene glycol solvent were put into a sand mill, the sand mill speed was set to 800 r / min, the sand mill time was 6 h, and the nanoparticle dispersion slurry was prepared for use;

[0125] S1-2, weigh a certain amount of nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1.25, and the nano-SiO 2 Relative to the total terephthalic acid content of 3000ppm;

[0126] The esterification polycondensation catalyst Sb with a content of 170 ppm relative to terephthalic acid 2 O 3 , 70ppm buffer NaH 2 PO 4 300ppm of stabilizer trimethyl phosphate is added to the nanoparticle dispersion slurry, stirred evenly and then put into the reactor, then terephthalic acid is slowly added into the reactor through the feed port, and finally ethylene glycol is added;

[0127] S1-3. After closing the reactor, nitrogen is slowly introduced, and the esterification temperature in the kettle is set to 245°C (the actual temperature is between 230 and 245°C) for reaction. When the water output reaches 95% of the theoretical water output, the esterification valve is turned off, and the pressure relief valve is opened to make the pressure in the kettle reach atmospheric pressure, and then the temperature is raised to 280°C, and the vacuum degree of the polymerization system is reduced by evacuation. When the vacuum degree of the system reaches 20Pa, the temperature is raised to 280°C, and the reaction is carried out for 150 minutes to discharge the material. 5 minutes before discharging, a capping agent PDMS accounting for 10 mol% of the total content of terephthalic acid is added to obtain an anti-hydrolysis masterbatch.

[0128] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0129] The anti-hydrolysis masterbatch was added into the melt extrusion system, melted at 280°C and then extruded, and quenched on a cold roller at 50°C to obtain an amorphous casting sheet with a thickness of 500 μm, and then the casting sheet was pulled into a stretching area, and the casting sheet was biaxially stretched by 2.0 times, and the film thickness after stretching was 125 μm to obtain a base film;

[0130] S3, spraying a hydrophobic coating on the base film to form a hydrophobic layer, and preparing a highly transparent and hydrolysis-resistant film:

[0131] S3-1, preparation of hydrophobic coating:

[0132] In terms of weight, a mixture of 1000 parts of ethyl acetate and 100 parts of polydimethylsiloxane was dispersed using an emulsifier for 10 minutes, and then 25 parts of nano-SiO 2 , SiO 2 After adding completely, continue to disperse for 15 minutes to form a uniform suspension, then add 4 parts of tetraethoxysilane, 1 part of dibutyl butyl dilaurate catalyst, and 1 part of benzotriazole derivative antioxidant Tinuvin 327 (2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole) and continue stirring for 1 minute. After the end, let it stand for 20 minutes to defoam to obtain a hydrophobic coating.

[0133] S3-2. Pre-clean the surface of the base film obtained above to remove surface dust, grease, etc., and then apply the hydrophobic coating on both sides of the base film at a distance of 35 cm by machine spraying. Then, place the composite film containing the coating liquid in an oven at 80°C and bake for 5 minutes to form a hydrophobic layer with a thickness of 75 nm, and finally obtain a highly transparent and hydrolysis-resistant film.

[0134] Comparative Example 4

[0135] A method for preparing a highly transparent and hydrolysis-resistant film, characterized in that it comprises the following steps:

[0136] S1. Preparation of hydrolysis-resistant masterbatch:

[0137] S1-1, according to the weight percentage, 25% of nano-SiO 2 / CaCO 3 Powder and 75% ethylene glycol solvent were put into the sand mill, among which SiO 2 、CaCO 3 The ratio was 1:1, the sand milling speed was set to 800 r / min, the sand milling time was 6 h, and the nanoparticle dispersion slurry was prepared for use;

[0138] S1-2, weigh a certain amount of nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1.25, and the nano-SiO 2 With nano-CaCO 3 The total content of the mixture relative to terephthalic acid is 3000ppm;

[0139] The esterification polycondensation catalyst Sb with a content of 170 ppm relative to terephthalic acid 2 O 3 , 70ppm buffer NaH 2 PO 4 300ppm of stabilizer trimethyl phosphate is added to the nanoparticle dispersion slurry, stirred evenly and then put into the reactor, then terephthalic acid is slowly added into the reactor through the feed port, and finally ethylene glycol is added;

[0140] S1-3. After closing the reactor, nitrogen is slowly introduced, and the esterification temperature in the kettle is set to 245°C (the actual temperature is between 230 and 245°C) for reaction. When the water output reaches 95% of the theoretical water output, the esterification valve is turned off, and the pressure relief valve is opened to make the pressure in the kettle reach atmospheric pressure, and then the temperature is raised to 280°C, and the vacuum degree of the polymerization system is reduced by evacuation. When the vacuum degree of the system reaches 20Pa, the temperature is raised to 280°C, and the reaction is carried out for 150 minutes to discharge the material. 5 minutes before discharging, a capping agent PDMS accounting for 10 mol% of the total content of terephthalic acid is added to obtain an anti-hydrolysis masterbatch.

[0141] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0142] The anti-hydrolysis masterbatch was added into the melt extrusion system, melted at 280°C and then extruded, and quenched on a cold roller at 50°C to obtain an amorphous casting sheet with a thickness of 500 μm, and then the casting sheet was pulled into a stretching area, and the casting sheet was biaxially stretched by 2.0 times, and the film thickness after stretching was 125 μm to obtain a base film;

[0143] S3, spraying a hydrophobic coating on the base film to form a hydrophobic layer, and preparing a highly transparent and hydrolysis-resistant film:

[0144] S3-1, preparation of hydrophobic coating:

[0145] In terms of weight, a mixture of 1000 parts of ethyl acetate and 100 parts of polydimethylsiloxane was dispersed using an emulsifier for 10 minutes, and then 25 parts of nano-SiO 2 , SiO 2 After adding completely, continue to disperse for 15 minutes to form a uniform suspension, then add 4 parts of tetraethoxysilane, 1 part of dibutyl butyl dilaurate catalyst, and 1 part of benzotriazole derivative antioxidant Tinuvin 327 (2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole) and continue stirring for 1 minute. After the end, let it stand for 20 minutes to defoam to obtain a hydrophobic coating.

[0146] S3-2. Pre-clean the surface of the base film obtained above to remove surface dust, grease, etc., and then apply the hydrophobic coating on both sides of the base film at a distance of 35 cm by machine spraying. Then, place the composite film containing the coating liquid in an oven at 80°C and bake for 5 minutes to form a hydrophobic layer with a thickness of 60 nm, and finally obtain a highly transparent and hydrolysis-resistant film.

[0147] Comparative Example 5

[0148] A method for preparing a highly transparent and hydrolysis-resistant film, characterized in that it comprises the following steps:

[0149] S1. Preparation of hydrolysis-resistant masterbatch:

[0150] S1-1, according to the weight percentage, 25% of nano-SiO 2 / CaCO 3 Powder and 75% ethylene glycol solvent were put into the sand mill, among which SiO 2 、CaCO 3 The ratio was 1:1, the sand milling speed was set to 800 r / min, the sand milling time was 6 h, and the nanoparticle dispersion slurry was prepared for use;

[0151] S1-2, weigh a certain amount of nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, so that the molar ratio of ethylene glycol to terephthalic acid is 1.25, and the nano-SiO 2 With nano-CaCO 3 The total content of the mixture relative to terephthalic acid is 3000ppm;

[0152] The esterification polycondensation catalyst Sb with a content of 170 ppm relative to terephthalic acid 2 O 3 , 70ppm buffer NaH 2 PO 4300ppm of stabilizer trimethyl phosphate is added to the nanoparticle dispersion slurry, stirred evenly and then put into the reactor, then terephthalic acid is slowly added into the reactor through the feed port, and finally ethylene glycol is added;

[0153] S1-3. After closing the reactor, nitrogen is slowly introduced, and the esterification temperature in the kettle is set to 245°C (the actual temperature is between 230 and 245°C) for reaction. When the water output reaches 95% of the theoretical water output, the esterification valve is turned off, and the pressure relief valve is opened to make the pressure in the kettle reach atmospheric pressure, and then the temperature is raised to 280°C, and the vacuum degree of the polymerization system is reduced by evacuation. When the vacuum degree of the system reaches 20Pa, the temperature is raised to 280°C, and the reaction is carried out for 150 minutes to discharge the material. 5 minutes before discharging, a capping agent PDMS accounting for 10 mol% of the total content of terephthalic acid is added to obtain an anti-hydrolysis masterbatch.

[0154] S2, preparing a base film by melt extrusion using the anti-hydrolysis masterbatch;

[0155] The anti-hydrolysis masterbatch was added into the melt extrusion system, melted at 280°C and then extruded, and quenched on a cold roller at 50°C to obtain an amorphous casting sheet with a thickness of 500 μm, and then the casting sheet was pulled into a stretching area, and the casting sheet was biaxially stretched by 2.0 times, and the film thickness after stretching was 125 μm to obtain a base film;

[0156] S3, spraying a hydrophobic coating on the base film to form a hydrophobic layer, and preparing a highly transparent and hydrolysis-resistant film:

[0157] S3-1, preparation of hydrophobic coating:

[0158] In terms of weight, a mixture of 1000 parts of ethyl acetate and 100 parts of polydimethylsiloxane was dispersed using an emulsifier for 10 minutes, and then 25 parts of nano-SiO 2 , SiO 2 After adding completely, continue to disperse for 15 minutes to form a uniform suspension, then add 4 parts of tetraethoxysilane, 1 part of dibutyl butyl dilaurate catalyst, and 1 part of benzotriazole derivative antioxidant Tinuvin 327 (2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole) and continue stirring for 1 minute. After the end, let it stand for 20 minutes to defoam to obtain a hydrophobic coating.

[0159] S3-2. Pre-clean the surface of the base film obtained above to remove surface dust, grease, etc., and then apply the hydrophobic coating on both sides of the base film at a distance of 35 cm by machine spraying. Then, place the composite film containing the coating liquid in an oven at 80°C and bake for 5 minutes to form a hydrophobic layer with a thickness of 100 nm, and finally obtain a highly transparent and hydrolysis-resistant film.

[0160] The high permeability and hydrolysis resistance films prepared in the examples and comparative examples were tested for relevant properties, and the test results are shown in Table 1 below:

[0161] Table 1

[0162]

[0163]

[0164] Note: Aging refers to 15 days in a 65℃ / 95%RH environment.

[0165] In the table:

[0166] Water contact angle: tested according to the method of standard GB / T 30693-2014;

[0167] Water vapor transmission rate: tested according to the method of standard GB / T 1037-2021;

[0168] Adhesion ASTM Grade Test: Tested according to the standard ASTM D 3359-2002 method.

[0169] Transmittance and haze test: Use the haze transmittance meter from Sannshi, model: YS6002-M desktop transmittance color haze meter.

[0170] -COOH (kg / mmol) test: tested according to the method of standard GBT 14190-2017.

[0171] According to the test results in Table 1, part of CaCO was mixed into the opening agent during the synthesis process of Example 1. 3 As an anti-hydrolysis inhibitor, a carboxyl end-capping agent is added before discharging, and the thickness of the super-hydrophobic coating is controlled at 75 nm, which can maximize the anti-aging effect in a humid environment. The high-transmittance anti-hydrolysis film prepared in this embodiment has a high water contact angle of 153° and a water vapor permeability of 3.34 g / (m 2 ·24h), the coating ASTM grade adhesion reaches grade 5B, the visible light transmittance and haze are 88.5% and 3.2% respectively, the yellowing index YI is 1.30, and the -COOH content is 9mmol / kg. After being placed in a 65℃ / 95%RH environment for 15 days, the visible light transmittance and haze are 86.6% and 3.9% respectively, the yellowing index YI is 2.09, and the -COOH content is 10mmol / kg. After aging, it still maintains high light transmittance and low haze value, and the -COOH content and yellowing index change very little, indicating that the film has excellent anti-hydrolysis performance.

[0172] The comparison between Comparative Examples 1-5 and Example 1 shows that the PET film can achieve the best anti-hydrolysis effect by using an anti-hydrolysis inhibitor in the synthesis stage and a terminal carboxyl capping agent after the synthesis.

[0173] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a highly transparent and hydrolysis-resistant film, characterized in that: The following steps are involved: S1, preparing hydrolysis-resistant masterbatch; The raw materials for preparing the hydrolysis-resistant masterbatch include: nano-SiO2, nano-CaCO3, ethylene glycol, terephthalic acid, esterification polycondensation catalyst, buffer, stabilizer, and end-capping agent; S2, preparing a base film by melt extrusion using the hydrolysis-resistant masterbatch; S3. Spray a hydrophobic coating on the base film to form a hydrophobic layer, thereby preparing a highly transparent and hydrolysis-resistant film.

2. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 1, characterized in that: Step S1 specifically includes: S1-1, take 15-40wt% of the mixture of nano-SiO2 and nano-CaCO3 and 60-85wt% of ethylene glycol, mix them and put them into a sand mill, sand mill them at 400-1600r / min for 3-12h to obtain a nanoparticle dispersion slurry, wherein the mass ratio of nano-SiO2 to nano-CaCO3 is 2:1-1:2; S1-2, weighing nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, satisfying that the molar ratio of ethylene glycol to terephthalic acid is 1-1.5, and the total content of the mixture of nano-SiO2 and nano-CaCO3 in the nanoparticle dispersion slurry relative to terephthalic acid is 1500-6000ppm; Adding 80-350 ppm of esterification polycondensation catalyst, 35-140 ppm of buffer and 150-600 ppm of stabilizer to the nanoparticle dispersion slurry relative to the terephthalic acid content, stirring evenly and then putting it into a reactor, then putting terephthalic acid into the reactor, and finally adding ethylene glycol; S1-3, after sealing the reactor, introduce nitrogen and react at 240-250°C. When the water output reaches more than 95% of the theoretical water output, heat it to 275-285°C and simultaneously evacuate the reactor for polycondensation. React for 130-170 minutes and discharge the material. Add a capping agent accounting for 5-20 mol% of the total terephthalic acid content 2-10 minutes before discharging the material to obtain a hydrolysis-resistant masterbatch.

3. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 2, characterized in that: Step S1 specifically includes: S1-1, take 25wt% of the mixture of nano-SiO2 and nano-CaCO3 and 75wt% of ethylene glycol, mix them and put them into a sand mill, sand mill them at 800r / min for 6h to obtain a nanoparticle dispersion slurry, wherein the mass ratio of nano-SiO2 to nano-CaCO3 is 1:1; S1-2, weighing nanoparticle dispersion slurry, ethylene glycol, and terephthalic acid, satisfying that the molar ratio of ethylene glycol to terephthalic acid is 1.25, and the total content of the mixture of nano-SiO2 and nano-CaCO3 in the nanoparticle dispersion slurry relative to terephthalic acid is 3000ppm; An esterification polycondensation catalyst with a content of 170 ppm relative to terephthalic acid, a buffer of 70 ppm, and a stabilizer of 300 ppm are added to the nanoparticle dispersion slurry, and after being stirred evenly, the mixture is put into a reactor, and then terephthalic acid is put into the reactor, and finally ethylene glycol is added; S1-3, nitrogen is introduced into the closed reactor, and the reaction is carried out at 240-250°C. When the water output reaches more than 95% of the theoretical water output, the temperature is raised to 275-285°C, and vacuum is drawn to carry out polycondensation reaction. The reaction lasts for 130-170 minutes and the material is discharged. 5 minutes before the discharge, a capping agent accounting for 5-20 mol% of the total terephthalic acid content is added to obtain a hydrolysis-resistant masterbatch.

4. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 1, characterized in that: The esterification polycondensation catalyst is selected from at least one of titanium glycolate, titanium dioxide, antimony glycolate, antimony oxide, germanium oxide, sodium metaaluminate, and sodium aluminosilicate; The buffer is selected from one or more of hydroxyethylpiperazine ethionine buffer, phosphate buffer, and 2-morpholineethylsulfonic acid buffer.

5. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 2, characterized in that: The stabilizer is selected from at least one of phosphoric acid, trimethyl phosphate, triphenyl phosphate, and triethyl phosphoacetate; The end-capping agent is selected from at least one of KH550, KH560, polydimethylsiloxane, and anilinemethyltriethoxysilane.

6. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 1, characterized in that: The raw materials for preparing the hydrophobic coating include, by weight: 500-2000 parts of solvent, 50-200 parts of modifier, 12-50 parts of nano-SiO2, 2-8 parts of organosilane, 0.1-2 parts of modified catalyst, and 0.5-2 parts of antioxidant.

7. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 6, characterized in that: Step S3 specifically includes: S3-1, preparation of hydrophobic coating: The solvent and the modifier are mixed and dispersed for 5-20 minutes, and then nano-SiO2 is added and dispersed for 5-30 minutes, and organic silane, modified catalyst and antioxidant are added, and stirred for 0.5-2 minutes. After the end, it is allowed to stand for 10-40 minutes to defoam, and a hydrophobic coating is obtained. S3-2, coating the hydrophobic coating on the upper and lower surfaces of the cleaned base film, baking at 70-90° C. for 2-10 minutes to form a hydrophobic layer with a thickness of 65-90 nm, and obtaining a highly transparent and hydrolysis-resistant film.

8. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 7, characterized in that: The solvent is selected from at least one of toluene, ethyl acetate, alcohol and butanone; The modifier is selected from at least one of tert-butyl acrylate, polydimethylsiloxane, and polydimethylsiloxane copolymer; The organosilane is selected from one of methyltriethoxysilane and tetraethoxysilane; The antioxidant is selected from at least one of alkyl dithiocarbamate zinc, mercaptobenzothiazole derivatives, and benzotriazole derivatives; The modified catalyst is dibutyl butyl dilaurate.

9. The method for preparing a highly transparent and hydrolysis-resistant film according to claim 1, characterized in that: Step S2 specifically comprises: melt-extrude the hydrolysis-resistant polyester masterbatch at 260-300° C., quench with a cold roller at 40-60° C. to obtain an amorphous casting sheet, and then biaxially stretch the sheet to obtain a base film.

10. A highly transparent and hydrolysis-resistant film, characterized in that: It is prepared by the method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-performance hydrolysis resistant PET (polyethylene terephthalate) master batch and preparation method thereof

    CN103627152A

  • A method for preparing hydrolysis-resistant polyester film

    CN109081929B

  • A high-barrier, hydrolysis-resistant solar cell backsheet and its preparation method

    CN111477711B

  • Applications of modified PET resin materials, solar cell backsheet films, and ultraviolet absorbers

    CN113321904B